Thermally Stabilised Poly(vinyl alcohol) Nanofibrous Materials Produced by Scalable Electrospinning: Applications in Tissue Engineering - Homer, W Joseph A; Lisnenko, Maxim; Hauzerova, Sarka; Heczkova, Bohdana; Gardner, Adrian C; Kostakova, Eva K; Topham, Paul D; Jencova, Vera; Theodosiou, Eirini (Polymers, 2024)
Electrospinning is a widely employed manufacturing platform for tissue engineering applications because it produces structures that closely mimic the extracellular matrix. Herein, we demonstrate the potential of poly(vinyl alcohol) (PVA) electrospun nanofibers as scaffolds for tissue engineering. Nanofibers were created by needleless direct current electrospinning from PVA with two different degrees of hydrolysis (DH), namely 98% and 99% and subsequently heat treated at 180 °C for up to 16 h to render them insoluble in aqueous environments without the use of toxic cross-linking agents. Despite the small differences in the PVA chemical structure, the changes in the material properties were substantial. The higher degree of hydrolysis resulted in non-woven supports with thinner fibres (285 ± 81 nm c.f. 399 ± 153 nm) that were mechanically stronger by 62% (±11%) and almost twice as more crystalline than those from 98% hydrolysed PVA. Although prolonged heat treatment (16 h) did not influence fibre morphology, it reduced the crystallinity and tensile strength for both sets of materials. All samples demonstrated a lack or very low degree of haemolysis (<5%), and there were no notable changes in their anticoagulant activity (≤3%). Thrombus formation, on the other hand, increased by 82% (±18%) for the 98% hydrolysed samples and by 71% (±10%) for the 99% hydrolysed samples, with heat treatment up to 16 h, as a direct consequence of the preservation of the fibrous morphology. 3T3 mouse fibroblasts showed the best proliferation on scaffolds that were thermally stabilised for 4 and 8 h. Overall these scaffolds show potential as 'greener' alternatives to other electrospun tissue engineering materials, especially in cases where they may be used as delivery vectors for heat tolerant additives.
Keywords: electrospinning; tissue engineering; cross-linking; poly(vinyl alcohol); non-woven fibres